Contact Less Food Ordering - L Jagadeesh; S. Noor Taj (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Contactless meal ordering has significantly transformed the way customers interact with restaurants. Through digital platforms, diners can effortlessly explore menu options, customize their meals, and finalize payments—all from their own devices. Here, the customer uses the restaurant QR code to order food. If a table is available, it will automatically reserve it for them; if not, they will be added to a waiting list and must choose their meal before paying the amount based on what they ordered for the table.
Keywords: Add Food info; Add Tables; Scan Qr code; choose Food for order; Waiting list; Payment